Die be-tekening van konsepte in die opvoedkunde met verwysing na standpuntverskille aangaande die skool en ouerhuis as gesagstrukture - Henning, O. A. (Koers, 1991)
In this article attention is focused upon the diversity of meanings that educationists attach to a societal relationship like the school. The opinion often appearing in literature on education that the school is an "extension" of the family and that the teacher can take action as a substitute parent is questioned in particular. By means of a cosmological analysis of the societal structures, school and family, an attempt is made to refute such statements. This variety of meanings which tend to cause confusion and are conveyed by the mentioned concepts in literature, is ascribed to the outcome of a diversity of paradigmatic and theoretical presuppositions.